Mental health in primary care, a new approach - edited by Andrew Elder and Jeremy Holmes (Oxford University Press, 2002)
Mental Health has finally come home to primary care, where 90% of all patients with psychological difficulties are diagnosed and treated, and where Governments increasingly see the bulk of mental health commissioning and practice as belonging. This book, whose contributors uniquely include leading figures from the world of both primary care and psychiatry, brings together the best of contemporary psychiatry with a deep understanding of the realities, challenges, and opportunities of general practice...